Developing the rural town of Panchor into a future river-based tourism destination: host community perception - Saad, Mazni; Abdullah, Nur Nabilah; Rosman, Siti Nur Hidayah (E-BPJ, 2020)
This paper examines the significance of a rural area, Panchor village town, as a potential nature tourism site in the Muar district of Johor, Malaysia. The objectives of the study were (1) to evaluate local community support and (2) to assess local community involvement. Based on qualitative analysis of an interview and open-ended responses in the questionnaire, three interconnected themes were: (1) community attachment, (2) economic gains and (3) environmental attitude. The findings revealed that river-based tourism development could stimulate the socio-economic status and the sustainability of rural areas. This study also discussed the implications and limitations of the research.